The schoolmaster ([England] : Pub. by G Humphrey, 24 St. James's Street, 1831)
"Brougham stands in profile to the left, playing diabolo with a tiny William IV, who dangles in ribbon looped between his two sticks..." (Source: George)
This record contains unverified data from George.
[Sharpshooter?].
Catalogue of Political and Personal Satires preserved in the Department of Prints and Drawings in the British Museum / by Mary Dorothy George
Forms part of: British Cartoon Prints Collection (Library of Congress).
Keywords: Cartoons (Commentary) -- British -- 1830-1840.; Engravings -- 1830-1840.